THAI BUSINESS CYCLE FROM MACROECONOMIC MODEL USING BVAR AND MS-BVAR METHODS - Siriphirunphong, Disorn; Chaiboonsri, Chukiat; Saosaovaphak, Anuphak (PEOPLE: International Journal of Social Sciences, 2015)
This study aims to determine the impact of important components of Thai business cycle during prosperity and depression phases. The BVAR and MS-BVAR models are used to analyze the relationship of each variable. The variables consist of population, GDP, inflation, balance of payments, government cash balance, interest rate, and exchange rate. The data correlated in this study are secondary data during 1979 to 2014 obtained from various sources including World Bank World Development Indicators and the Global Development Finance database, World Resources Institutes (WRI), and Bank of Thailand (BOT). The results of this study indicate that each variable in this model has statistical significant relationship. From the analysis, each variable has different impact on Thai business cycle during prosperity and depression phases.